Yönetici hemşirelerin duygusal zekâ yetenekleri ve liderlik davranışları - (:unkn) unknown (My University, 2012)
Amaç: Araştırma yönetici hemşirelerin duygusal zekâ yetenekleri (DZY) ve liderlik davranışlarını (LD) belirlemek amacıyla yapılmıştır. Yöntem:Araştırma tanımlayıcı nitelikte olup; evrenini İstanbul ilinde farklı statülerdeki hastanelerde çalışan 1500 yönetici hemşire, örneklemini ise çalışmayı kabul eden 258 kişi oluşturmuştur. Veri toplama aracı; bilgi formu , DZY ve LD ölçekleridir. Bulgular: Yönetici hemşirelerin DZY (3.92±0.32) ve LD (3.81±0.27) ortalamanın üzerinde, DZY ile LD arasında pozitif yönde yüksek ilişki saptanmıştır (r=0.72,p<0.01). Sonuç: Yönetici hemşirelerin DZY ve LDna sahip olduklarını göstermiştir.

Aim: The research was applied descriptively was obtained in order to determine the EQ skills and leadership attitudes (LA) of nurse manager. Method:The research as descriptive; population of different statuses in Istanbul nurse managers working in hospitals in 1500, formed the sample of 258 people who accepted to work. Information form, EQ skills and LA measures were used as data collection means. Results: The findings of the research indicated that EQ skills (3.92±0.32), LA points (3.81±0.27) of nurse managers are at a good level. A positive linear relation (r=0.72,p<0.01) was found between EQ skills and LA of nurse managers. Conclusion: Depending on these results, it is stated that nurse managers have EQ skills and LA and it s recommended that.
The emotional intelligence skills & leadership attitudes of nurse manager
Keywords: Eğitim, Eğitim Araştırmaları; Hemşirelik